61.2k views
1 vote
Your answer should be a polynomial in standard form. (x + 5)(x +3)=(x+5)(x+3)

1 Answer

6 votes

Answer:

∴(x+5)(x+3) =x²+8x+15

Explanation:

Standard form of a polynomial:

Standard of polynomial means that the terms ordered from biggest exponent of variable to lowest exponent of variable.

Example:


a_nx^n+a_(n-1)x^(n-1)+a_(n-2)x^(n-2)+......

Given,

(x+5)(x+3)

=x(x+3)+5(x+3)

=x²+3x+5x+15

=x²+8x+15

∴(x+5)(x+3) =x²+8x+15

The degree of the polynomial is 2 and is a one variable polynomial.

User Malbs
by
5.1k points